Deletion of BST2 Cytoplasmic and Transmembrane N-Terminal Domains Results in SARS-CoV, SARS-CoV-2, and Influenza Virus Production Suppression in a Vero Cell Line - Dolskiy, Alexander A.; Bodnev, Sergei A.; Nazarenko, Anastasia A.; Smirnova, Anastasia M.; Pyankova, Olga G.; Matveeva, Anna K.; Grishchenko, Irina V.; Tregubchak, Tatiana V.; Pyankov, Oleg V.; Ryzhikov, Alexander B.; Gavrilova, Elena V.; Maksyutov, Rinat A.; et al. (Frontiers in Molecular Biosciences, 2020)
SARS-CoV-2, which emerged in Wuhan (China), has become a great worldwide problem in 2020 and has led to more than 1,000,000 deaths worldwide. Many laboratories are searching for ways to fight this pandemic. We studied the action of the cellular antiviral protein tetherin, which is encoded by the BST2 gene. We deleted the transmembrane domain-encoding part of the gene in the Vero cell line. The transmembrane domain is a target for virus-antagonizing proteins. We showed a decrease in SARS-CoV-2 in cells with deleted transmembrane BST2 domains compared to the initial Vero cell line. Similar results were obtained for SARS-CoV and avian influenza virus. This finding may help the development of antiviral therapies competitively targeting the transmembrane domain of tetherin with viral-antagonizing proteins.